1980
DOI: 10.1007/bf03007047
|View full text |Cite
|
Sign up to set email alerts
|

Incentive spirometry: Its value after cardiac surgery

Abstract: Treatment with intermittent positive pressure breathing (1PPB) and incentive spirometry (I.S.) was compared in 109 patients after heart surgery with cardiopulmonary bypass. Assessment was done by measurement of vital capacity, arterial oxygen tension and identifica-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
2

Year Published

1985
1985
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 11 publications
1
28
0
2
Order By: Relevance
“…Two main areas of investigation have been pursued: incentive spirometry for PPC prevention following upper abdominal surgery, [30][31][32][33][34][35][36][37][38][39][40][41][42][43] and incentive spirometry for PPC prevention following cardiac/thoracic surgery. [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] Comparison of these studies is difficult, owing to the various study designs (randomized controlled trials and prospective trials), the comparators (none, chest physical therapy [CPT], CPAP, expiratory airway pressure), the frequency of interventions (eg, hourly, every 4 hours), the duration of each intervention (number of maneuvers, minutes of therapy), and the outcomes (radiographic atelectasis, gas exchange, pneumonia, pulmonary function). Of the studies that used PPCs as an outcome, 3 compared incentive spirometry with a control group of no intervention following upper abdominal surgery.…”
Section: Incentive Spirometrymentioning
confidence: 99%
See 2 more Smart Citations
“…Two main areas of investigation have been pursued: incentive spirometry for PPC prevention following upper abdominal surgery, [30][31][32][33][34][35][36][37][38][39][40][41][42][43] and incentive spirometry for PPC prevention following cardiac/thoracic surgery. [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] Comparison of these studies is difficult, owing to the various study designs (randomized controlled trials and prospective trials), the comparators (none, chest physical therapy [CPT], CPAP, expiratory airway pressure), the frequency of interventions (eg, hourly, every 4 hours), the duration of each intervention (number of maneuvers, minutes of therapy), and the outcomes (radiographic atelectasis, gas exchange, pneumonia, pulmonary function). Of the studies that used PPCs as an outcome, 3 compared incentive spirometry with a control group of no intervention following upper abdominal surgery.…”
Section: Incentive Spirometrymentioning
confidence: 99%
“…[31][32][33]35,37,40 Studies comparing incentive spirometry for PPC prevention after cardiac/thoracic surgery also include a trial with no intervention as the control, 48 and studies that compared incentive spirometry to other techniques. 44,45,47,48,51,52,54,55,58,60 The majority of these trials reported no difference between incentive spirometry and the comparator. 44,47,48,51,52,54,58,60 This creates one of the challenges in evaluating the evidence on incentive spirometry in PPC prevention.…”
Section: Incentive Spirometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Another intervention vs. IS: Nine studies evaluated the incidence of PPC 37,38,40,41,44,45,47,48,51 . One study 38 showed that the use of IS associated to exercises with positive pressure (EPAP) reduced the incidence of PPC in patients undergoing surgery for myocardial revascularization when compared with deep breathing (Table 4).…”
Section: Ppc As An Outcomementioning
confidence: 99%
“…Another intervention vs. IS: Eight studies evaluated the lung function as an outcome 37,39,40,[43][44][45]47,52 , being two studies 44,47 , the IS improved the lung function when compared to other physical therapy interventions. One study 39 showed that the IS did not restore the lung function after surgery when compared to the use of exercises with positive pressure.…”
Section: Lung Function As An Outcomementioning
confidence: 99%